2008
DOI: 10.1515/mamm.2008.045
|View full text |Cite
|
Sign up to set email alerts
|

Small-mammal assemblage response to deforestation and afforestation in central China

Abstract: Deforestation is a major environmental issue driving the loss of animal and plant species. Afforestation has recently been promoted to conserve and restore Chinese forest ecosystems. We investigated the distribution of small-mammal assemblages in an area where forest and associated deforestation habitats dominate and in an agricultural area where afforestation is ongoing in the Loess Plateau of southern Ningxia Autonomous Region, P.R. China. Multiple trapping was used. Assemblages were defined based on the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 34 publications
0
48
2
Order By: Relevance
“…All these transmission hotspots share the fact that a number of small mammal intermediate host species were prone to population outbreaks during the study period, indicated by large trapping success and small mammal activity indices (Giraudoux et al 1998; Raoul et al 2006, 2008). Small mammal population surges were also found in Narati and Baihaba in Xinjiang (China), however they appeared not to translate into human AE prevalence levels as large as in the other sites highlighted above.…”
Section: Human Ae Hotspots In China and Neighbouring Countriesmentioning
confidence: 94%
“…All these transmission hotspots share the fact that a number of small mammal intermediate host species were prone to population outbreaks during the study period, indicated by large trapping success and small mammal activity indices (Giraudoux et al 1998; Raoul et al 2006, 2008). Small mammal population surges were also found in Narati and Baihaba in Xinjiang (China), however they appeared not to translate into human AE prevalence levels as large as in the other sites highlighted above.…”
Section: Human Ae Hotspots In China and Neighbouring Countriesmentioning
confidence: 94%
“…It has been shown that sampling in all habitats is important for understanding small mammal community changes in forest-farmland ecosystems (Panzacchi et al 2010). For example, quite unexpectedly, newly afforested sites may harbour a poor small mammal diversity in comparison to habitat undergoing deforestation -for the first 15 years at least, newly afforested habitats in China were found to be dominated by agricultural pest species (Raoul et al 2008). For the first four years of afforestation, small mammals do not tend to react to it, as could be the case in other types of disturbances that fragment their habitat (Johnson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Small mammal species often exhibit specific preferences for optimal habitats, with species distributions influenced by the locations of these key habitats (Raoul et al ., 2008). Small mammal populations are shown to respond to optimal habitat availability, particularly the ratio of optimal habitat to total land area (Giraudoux et al ., 2003; Pleydell et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This process is hypothesised to be significant for Em transmission (Giraudoux et al ., 1997), so that pathogen transmission may vary through time and space due to landscape modification. Elsewhere in China, small mammal spatial distributions are shown to be modified by landscape disturbances such as deforestation in Gansu (Giraudoux et al ., 1998), afforestation in Ningxia (Raoul et al ., 2008), and overgrazing and fencing practices on the Tibetan plateau (Wang et al ., 2004; Raoul et al ., 2006). …”
Section: Introductionmentioning
confidence: 99%